2014
DOI: 10.4077/cjp.2014.bac200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Scutellarein on Proliferation of Human Lung Cancer A549 Cells through ERK and NFκB Mediated by the EGFR Pathway

Abstract: High expression levels of cyclooxygenase-2 (COX-2) contribute a strong proliferative ability to human lung cancer cells, and this function is link to the epidermal growth factor receptor (EGFR) pathway, which was mediated by extracellular-signal-regulated kinase (ERK) and nuclear factor kappa B (NFκB). In this study, scutellarein, a flavonoid compound, was screened for proliferation inhibition at different concentrations (0, 5, 25 and 50 μM) at 24 h or 48 h in human lung cancer cell line A549. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…The reduction of p-EGFR and p-Akt decreased in the early time point and increased during the late time point, a trend that may be associated with melanogenesis inducer a-MSH. 20,21 These results suggest that the moderate miR-21-induced activation of EGFR/ Akt accounts for the anti-melanogenic effect in UV ray-radiated cells.…”
Section: Discussionmentioning
confidence: 94%
“…The reduction of p-EGFR and p-Akt decreased in the early time point and increased during the late time point, a trend that may be associated with melanogenesis inducer a-MSH. 20,21 These results suggest that the moderate miR-21-induced activation of EGFR/ Akt accounts for the anti-melanogenic effect in UV ray-radiated cells.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, it was reported that scutellarein improved micro-circulation and cerebral blood flow 42) and inhibited cancer cell proliferation and metastasis. 43,44) Scutellarein could also decrease platelet aggregation in spontaneously hypertensive rats. 19) In a recent paper published by Yan et al, 45) scutellarein dose-dependently depressed arterial or venous thrombosis in vivo, and restricted the rate of ADP-induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…It has many biochemical activities, including targeting of the phosphoinositide 3-kinase (PI3K)/ Akt signaling pathway, upregulation of tumor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL) death receptors DR4/DR5 expression in a p53-dependent manner, inhibition of glutamine metabolism, and induction of the epidermal growth factor receptor (EGFR) pathway. [7][8][9][10] However, the clinical use of apigenin is restricted, owing to its poor biopharmaceutical properties, including water insolubility and poor absorption. 11 Although apigenin is predicted to be safe for lung cancer treatment, similar to the majority of antitumor drugs, resistance could develop during the course of treatment, which could result in therapeutic failure.…”
Section: Introductionmentioning
confidence: 99%